Genetic divergence based on quantitative variation for some seed traits in plus trees of neem (Azadirachta indica A. Juss) - Dhillon, R.S.; Verma, R.C.; Dhanda, S.K.; Sheokand, R.; Kumari, S. (Indian Journal of Agroforestry, 2020)
Genetic diversity among ninety-nine plus trees of neem (Azadirachta indica A. Juss) selected from different parts of Haryana and Delhi was studied for morphological and biochemical characters of seed using Mahalanobis D2 analysis. These trees were grouped into nine clusters. The clustering pattern indicated that geographical diversity did not have one to one relationship with genetic diversity in neem. The cluster IV was the largest and consisted of 19 trees followed by cluster IX and cluster V with 15 and 14 trees, respectively. The clusters III and VI were smallest with three trees each. The remaining clusters contained 10 to 12 trees. Intra cluster D2 values revealed that cluster V was most diverse (3.501) followed by cluster III (3.303) and cluster IV (3.261). Maximum inter-cluster distances were observed between clusters II and VI (8.576) followed by between clusters II and III (6.545), III and VIII (6.337) and clusters I and VI (6.315). Minimum distance was observed between cluster VIII and IX (3.474). On the basis of high cluster mean and wide genetic distance, the superior plus trees of cluster III (plus trees # 4,9.70) and VI (plus trees # 82,84,88) may be used as potential parents for hybridization in neem tree improvement programme.